BETWEEN GLOBALIZATION AND ANTI-TERROR: TRANSFORMATION OF THE DAGHESTAN ISLAMIC COMMUNITY IN THE POST-SOVIET PERIOD - A. K. Magomedov; D. G. Mirzakhanov (Современная наука и инновации, 2022)
Post-Soviet development of Islam in Dagestan took place in specific political conditions than, for example, in another large Muslim Republic - Tatarstan. The differences were due to the peculiarities of the development of the North Caucasus and, most importantly, the political situation in the region in the 1990s.